Coarse-grained simulations of the membrane-active antimicrobial Peptide maculatin 1.1. - Bond, P; Parton, D; Clark, J; Sansom, MS (2008)
Maculatin 1.1 (M1.1) is a membrane-active antimicrobial peptide (AMP) from an Australian tree frog that forms a kinked amphipathic alpha-helix in the presence of a lipid bilayer or bilayer-mimetic environment. To help elucidate its mechanism of membrane-lytic activity, we performed a total of approximately 8 micros of coarse-grained molecular dynamics (CG-MD) simulations of M1.1 in the presence of zwitterionic phospholipid membranes. Several systems were simulated in which the peptide/lipid ratio was varied. At a low peptide/lipid ratio, M1.1 adopted a kinked, membrane-interfacial location, consistent with experiment. At higher peptide/lipid ratios, we observed spontaneous, cooperative membrane insertion of M1.1 peptide aggregates. The minimum size for formation of a transmembrane (TM) aggregate was just four peptides. The absence of a simple and well-defined central channel, along with the exclusion of lipid headgroups from the aggregates, suggests that a pore-like model is an unlikely explanation for the mechanism of membrane lysis by M1.1. We also performed an extended 1.25 micros simulation of the permeabilization of a complete liposome by multiple peptides. Consistent with the simpler bilayer simulations, formation of monomeric interfacial peptides and TM peptide clusters was observed. In contrast, major structural changes were observed in the vesicle membrane, implicating induced membrane curvature in the mechanism of active antimicrobial peptide lysis. This contrasted with the behavior of the nonpore-forming model peptide WALP23, which inserted into the vesicle to form extended clusters of TM alpha-helices with relatively little perturbation of bilayer properties.